Analisis Beban Kerja dan Kebutuhan Sumber Daya Manusia Petugas Rekam Medis Puskesmas Adan-adan Kabupaten Kediri - Hikmawan Suryanto (Jurnal Rekam Medis dan Informasi Kesehatan, 2020)
Human resources are an important and vital component in an organization's operations. Quality health services can not be separated from the organization of a good medical record. In order to run well, sufficient medical records are needed. In the Adan-Adan Health Center, the number of patient visits from July 2018 to July 2019 was 16,828 people. Medical records officer only numbered 1 person. The research objective is to calculate the needs of human resources in the medical record unit using the ABK method. The design of this research is descriptive observational with case study approach. Respondents in this study were medical staff at the Adan-adan Health Center in Kediri Regency with a total of 1 person. The results of the study are that there is a shortage of human resources in the Adan-Adan Health Center medical record unit which should be 3, but totaling 1 person. Suggestions for Adan-Adan Health Center are employee recruitment needs to be done so that the number of medical records officers can be fulfilled. AbstrakSumber daya manusia merupakan komponen penting dan vital dalam operasional sebuah organisasi. Pelayanan kesehatan yang bermutu tidak terlepas dari penyelenggaraan rekam medis yang baik. Agar berjalan dengan baik, maka dibutuhkan sumber daya rekam medis yang cukup. Kunjungan pasien di Puskesmas Adan-adan pada periode Juli 2018 – Juli 2019 sebesar 16.828 orang. Petugas rekam medis hanya berjumlah 1 orang. Tujuan penelitian untuk menghitung kebutuhan sumber daya manusia di unit rekam medis menggunakan metode ABK. Desain penelitian ini yaitu observasional deskriptif dengan pendekatan case study. Responden dalam penelitian ini yaitu petugas rekam medis Puskesmas Adan-adan Kabupaten Kediri yang bejumlah 1 orang. Hasil penelitian yaitu terdapat kekurangan jumlah sumber daya manusia di unit rekam medis Puskesmas Adan-adan yang seharusnya berjumlah 3, namun saat ini berjumlah 1. Saran bagi Puskesmas Adan-adan yaitu perlu dilakukan rekrutmen pegawai agar jumlah petugas rekam medis dapat terpenuhi.